2016
DOI: 10.1111/1440-1681.12672
|View full text |Cite
|
Sign up to set email alerts
|

c‐Met inhibition enhances chemosensitivity of human ovarian cancer cells

Abstract: In clinical practice, human ovarian cancer shows considerable resistance to chemotherapy. This study aimed to investigate the role of c-Met in the chemoresistance of ovarian cancer. Ovarian cancer cell line SKOV3 and OVCAR-3 were pretreated with c-Met inhibitor INCB28060, and then treated with paclitaxel. Cell survival, cell cycle and apoptosis were analyzed by MTT assay, flow cytometry analysis and TUNEL assay, respectively. The activation of c-Met signalling was detected by western blot analysis. INCB28060 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Capmatinib (INC280) blocks c-Met phosphorylation and the activation of key downstream molecules in c-Met-dependent tumor cell lines, causing mitochondrial membrane depolarization and DNA repair [ 96 , 97 ]. The drug has been utilized in phase I trials for advanced solid cancer.…”
Section: Current Clinical Trials Targeting C-metmentioning
confidence: 99%
See 1 more Smart Citation
“…Capmatinib (INC280) blocks c-Met phosphorylation and the activation of key downstream molecules in c-Met-dependent tumor cell lines, causing mitochondrial membrane depolarization and DNA repair [ 96 , 97 ]. The drug has been utilized in phase I trials for advanced solid cancer.…”
Section: Current Clinical Trials Targeting C-metmentioning
confidence: 99%
“…The drug has been utilized in phase I trials for advanced solid cancer. Wei et al [ 96 ] found that the addition of capmatinib could effectively block cell proliferation induced by cancer associated fibroblast (CAF) matrix with overexpression of HGF, and could eliminate CAF-induced ovarian cancer cell resistance. The latest study by Lara et al [ 97 ] utilized a series of NSCLC cell lines (including three EGFR-mutant cell lines, HCC827, PC9 and H1975, one Kirsten rat sarcoma virus oncogene mutant cell line, H358, and one EGFR and KRAS wild type cell line, H1666) to determine whether capmatinib in combination with erlotinib could attenuate erlotinib resistance.…”
Section: Current Clinical Trials Targeting C-metmentioning
confidence: 99%
“…The tyrosine kinase c-Met, also called MET and hepatocyte growth factor receptor (HGFR), is a key regulator of organ development and cancer progression and has been studied in many cancer types such as lung cancer, gastric cancer, prostate cancer and so on [ 4 7 ]. c-Met inhibitors also have been tested in many cancers and shown promising results in lung cancer, ovarian cancer and so on [ 5 , 8 ]. In breast cancer, previous studies have yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking c-Met expression may overcome the resistance of cancer cells to cisplatin [34]. After treatment with crizotinib, cisplatin-induced proliferation inhibition and apoptosis were observed [35]. The long-term efficacy of crizotinib was found in several malignant tumors with MET amplification such as gastric and renal carcinoma [36,37].…”
Section: Gene Mutation In Omctsmentioning
confidence: 99%